2010
DOI: 10.1177/1359105309360072
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Life Satisfaction and Burnout in French Anaesthetists

Abstract: The present study aimed to examine the prevalence of burnout, levels of life satisfaction and job satisfaction in anaesthetists in France. A cross-sectional study was conducted among 193 anaesthetists from eight French public hospitals. The results indicated low levels of emotional exhaustion and depersonalization scores, but high levels of reduced accomplishment. The results also revealed differences between subgroups: physician anaesthetists reported higher levels of depersonalization and reduced accomplishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 34 publications
3
61
2
6
Order By: Relevance
“…When the three aspects of burnout are individually assessed as seen in Table 5, the results from the AS were comparable with scores obtained in other studies. 11,13,17,19 As the sample size was not determined for Private doctors a true comparison cannot be made.…”
Section: Discussionmentioning
confidence: 99%
“…When the three aspects of burnout are individually assessed as seen in Table 5, the results from the AS were comparable with scores obtained in other studies. 11,13,17,19 As the sample size was not determined for Private doctors a true comparison cannot be made.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel zur generellen Diskussion des Burn-out-Syndroms wurde in den vergangenen Jahren eine Reihe empirischer Untersuchungen zu diesem Thema bei Ärzten und Pflegekräften durchgeführt. Die implizite oder explizite Grundannahme hierbei war, dass gerade diese Berufsgruppen zufolge ihrer berufsbedingten Belastungen auffällig häu-fig von chronischer Überlastung betroffen sind -besonders in den Bereichen Psychiatrie, Onkologie, Anästhesie sowie Intensiv-und Notfallmedizin [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29].…”
Section: Prävalenz Und Determinanten Beruflicher üBerlastungunclassified
“…Chiron et al [12] haben in einer vor Kurzem publizierten Umfrage unter 193 Anästhesisten und Anästhesiefach-pflegekräften an 8 französischen Krankenhäusern u. a. anhand des MBI die Prä-valenz von Burn-out sowie den Grad der Arbeits-und der Lebenszufriedenheit ermittelt. Von der ursprünglichen Studienpopulation konnten 77 Fragebögen von nichtärztlichen und 74 Fragebögen von ärztlichen Teilnehmern ausgewertet werden.…”
Section: Prävalenz Und Determinanten Beruflicher üBerlastungunclassified
“…A French health psychology study by Chiron et al [5] found that anaesthesiologists and NAs developed a strategy of depersonalization and a cynical attitude to protect against stress and cope with the workload [5]. In contrast, a study by Pape & Dingman [6] revealed how the NAs' strategy during the induction process was to "get in their bubble", shielding the patient from the rest of the operating theatre staff and trying to promote her/his sense of being in focus.…”
Section: Introductionmentioning
confidence: 99%
“…The NA's presence at the threshold of unconsciousness encompasses not only her/his skill but also ethics and knowledge of how to manage the patient's life from induction to emergence [3,5]. Thus, the NA embodies the foundation on which the patient places trust and reliance for her/his selfpreservation [1].…”
Section: Introductionmentioning
confidence: 99%